2021
DOI: 10.3390/foods10091995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In Vitro Digestion on the Antioxidant Compounds and Antioxidant Capacity of 12 Plum (Spondias purpurea L.) Ecotypes

Abstract: Spondias purpurea L. plum is a source of antioxidant compounds. Nevertheless, once they are consumed and go through the digestive system, these compounds may undergo changes that modify their bioaccessibility. This study aimed to evaluate the effect of in vitro gastrointestinal digestion on the total content of carotenoids (TCC), ascorbic acid (AA), phenolic compounds (TPC), flavonoids (TFC), anthocyanins (TAC), and antioxidant capacity (ABTS, DPPH) of 12 plum Spondias purpurea L. ecotypes. The plum samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Unlike many low molecular weight compounds, AsA mounts a characteristic behavior during digestion. AsA is mainly released during gastric digestion, which could be assigned to a range of factors in the tract like enzymes, pH, and temperature in the gastrointestinal tract (Sollano-Mendieta et al 2021 ). The pharmacokinetics of AsA is mainly regulated by a family of saturable sodium-dependent vitamin C transporters (SVCTs) (Tsukaguchi et al 1999 ).…”
Section: Role Of Asa In Plantsmentioning
confidence: 99%
“…Unlike many low molecular weight compounds, AsA mounts a characteristic behavior during digestion. AsA is mainly released during gastric digestion, which could be assigned to a range of factors in the tract like enzymes, pH, and temperature in the gastrointestinal tract (Sollano-Mendieta et al 2021 ). The pharmacokinetics of AsA is mainly regulated by a family of saturable sodium-dependent vitamin C transporters (SVCTs) (Tsukaguchi et al 1999 ).…”
Section: Role Of Asa In Plantsmentioning
confidence: 99%
“…Recovery Index of AA, DHA and total vitamin C (AA+DHA) in the extract was significantly (p ≤ 0.05) higher (49.64%, 82.09% and 88.81%, respectively) in comparison to that obtained after intestinal digestion (BI) for all compounds (40.21% for AA, 18.26% for DHA and 20.01 for total vitamin C). Research works have reported losses of ascorbic acid after digestion with pepsin [15]. Studies have reported that ascorbic acid was more stable in acidic conditions than in alkaline [15].…”
Section: Recovery and Bioaccessibility Indices Of Bioactive Compounds...mentioning
confidence: 99%
“…Research works have reported losses of ascorbic acid after digestion with pepsin [15]. Studies have reported that ascorbic acid was more stable in acidic conditions than in alkaline [15]. During the gastric stage, the hydrochloric acid lowered the pH to 2.5, which might help to increase the ascorbic acid stability.…”
Section: Recovery and Bioaccessibility Indices Of Bioactive Compounds...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting study, with industrial byproducts from another fruit of the Spondias genus, the umbu (Spondias tuberosa L.), found high antioxidant power (DPPH 2440.3 µMTEAC/100 g of dry weight) [12]. A survey that evaluated 12 different ecotypes of Spondias purpurea L. identified ABTS contents that ranged from ~8.23 mMTEAC/100 g to ~1.89 mMTEAC/100 g [37] in one of the kinds of fresh fruit. Another set of research results demonstrates the high antioxidant power both in taperebá and in other fruits of the Spondias genus.…”
Section: Quantification Of Total Phenolics and Evaluation Of The Anti...mentioning
confidence: 99%